The Effectiveness of Local Micro-Video-Based Education (Health Microclips) in Preventing Acute Respiratory Infections Among Families with Toddlers in the Service Area of the Molompar Community Health Center, Southeast Minahasa Regency - Felix Eliezer Massie; Diana Vanda Daturara Doda; Jeanette Irene Christiene Manoppo; Dina Victoria Rombot; Margareth Rosalinda Sapulete (Al Makki Publisher, 2026)
Acute Respiratory Infection (ARI) is one of the leading causes of morbidity and mortality among children under five years of age in Indonesia. This study aimed to examine the effectiveness of local micro-video-based education (Health Microclips) in preventing ARI among families with toddlers in the service area of Molompar Community Health Center, Southeast Minahasa Regency. A pre-experimental design using a one-group pretest–posttest approach was employed. A total of 162 respondents were selected using purposive sampling. Data were collected using validated questionnaires measuring knowledge, attitudes, and preventive practices related to ARI prevention. The intervention was delivered through local micro-videos distributed via WhatsApp. Data were analyzed using the Wilcoxon Signed-Rank Test. The results showed that the proportion of respondents with good knowledge increased from 32.1% to 79.6%, positive attitudes increased from 56.2% to 88.9%, and good preventive practices increased from 63.6% to 85.2%. The Wilcoxon test results showed a p-value of 0.000 (p < 0.05) for all variables. It was concluded that local micro-video-based education (Health Microclips) was effective in improving knowledge, attitudes, and preventive practices related to ARI prevention among families with toddlers.